National Security and Conflict Prevention Strategies in Nigeria: The Place of Inclusive Peace Education - OLADIMEJI, Abdul-Warith Opeyemi; ABIOLA, Ebenezer Damilola; ADEBAJO, Mosimininuoluwa (Ilorin Journal of Education, 2023)
Education is said to be everyone's right, and it should be available to all members of society, regardless of ethnicity, socioeconomic status, gender, or geographical location. In this regard, peace is also everyone's right, and peace education should be the primary solution to all social conflicts in society. Nigeria, a populous country with numerous national security challenges, is experiencing an increased or heightened state of perpetual insecurity. This significantly slows the growth and development of Nigeria. It has become a top priority to address the root causes of the rising tide of insecurity in a bid to prevent conflicts. This paper gives an overview of the country's security issues and conflicts. It also assesses the initiatives being put in place to curtail insecurity as well as the strategies mostly used for conflict prevention to proffer a lasting solution. The study further examined the importance of inclusive peace education in reducing conflicts’ emergence, spread, and intensity. Peace education is now acknowledged as a potent tool for managing and preventing conflicts, and by extension, upholding national security. The paper concluded that early, inclusive, and comprehensive peace education are key to reducing conflict and maintaining national security in the critical phase Nigeria is in.